IBN SINA'S VIEWS ON MEDICINAL PLANTS - Yuldasheva Zarofat Igamberdiyevna; Rahmatullayeva Mahfuza Igamberdiyevna (Web of Journals Publishing, 2024)
Looking through the treatises of the great medieval doctor Abu Ali Husayn ibn Abdullah ibn Sina or Avicenna (980-1037), one can find many interesting medical knowledge and advice. Separately, the doctor talks about some medicinal plants and describes their capabilities and properties. Here are some of the doctor's observations.
Keywords: Ibn Sina, scientist, doctor, health, healthy, hygiene, plant, medicinal